Fatigue does not conjointly alter postural and cognitive performance when standing in a shooting position under dual-task conditions - Bermejo, J. L.; Garcia-Massó, X.; Paillard, T.; Noé, F. (Journal of Sports Sciences, 2018)
This study investigated the effects of fatigue on balance control and cognitive performance in a standing shooting position. Nineteen soldiers were asked to stand while holding a rifle (single task - ST). They also had to perform this postural task while simultaneously completing a cognitive task (dual task - DT). Both the ST and DT were performed in pre- and post-fatigue conditions. In pre-fatigue, participants achieved better balance control in the DT than in the ST, thus suggesting that the increased cognitive activity associated with the DT improves balance control by shifting the attentional focus away from a highly automatised activity. In post-fatigue, balance control was degraded in both the ST and DT, while reaction time was enhanced in the first minutes following the fatiguing exercise without affecting the accuracy of response in the cognitive task, which highlights the relative independent effects of fatigue on balance control and cognitive performance.